Novel process design for waste energy recovery of LNG power plants for CO2 capture and storage. (1st February 2023) - Lim, Jonghun; Kim, Yurim; Cho, Hyungtae; Lee, Jaewon; Kim, Junghwan
Highlights: Novel waste energy recovery process for carbon capture and storage was developed. Waste cold and hot energy from liquefied natural gas plant is recovered. Net power generation can increased by 16% compared to base process. Net profit can increased by 75% compared to base process. Abstract: In an liquefied natural gas (LNG) power plant, the amine scrubbing and CO2 liquefaction process are generally employed for CO2 capture and storage (CCS) because it is suitable for large-scale plants. However, a large amount of hot and cold energy is required for CO2 absorption, regeneration and liquefaction. As a solution, the waste LNG cold energy from the LNG regasification process and waste hot energy from natural gas combined cycle (NGCC), which are generally disposed into the seawater, can be recovered and utilized for the abovementioned purposes. Hence, this study suggested a novel process for waste hot and cold energy recovery of the LNG power plants for CCS. The suggested process model consists of the following four steps: LNG regasification, natural gas combined cycle, CO2 capture and regeneration and CO2 liquefaction. In the process model, the waste LNG cold energy is recovered at the lean amine cooler in the CO2 capture process and each heat exchanger in the CO2 liquefaction process. Furthermore, for CO2 regeneration, the waste hot energy from NGCC is recovered at the stripper reboiler. The exergy and economic analyses were addressed to evaluate the economic feasibility of energy conversion of the proposed process. As a result, compared to the base process, the net power generation and exergy efficiency of the proposed process increased by 16% and 8%, respectively. In addition, the net profit of the proposed process increased by 75%, indicating high economic feasibility. The overall energy efficiency and economic feasibility using waste cold and hot energy were observed to increase, which resulted in decreased fuel usage. Therefore, we believe that the proposed approach can contribute significantly to the economic improvements and environmental protection efforts.